The Effect of Hypertension Exercise on Blood Pressure in the Elderly: Experimental Quasy Study - Arita Murwani; Hadi Ashar; Gani Apriningtyas Budiyati (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Hypertension is the most common disease suffered by the elderly, this is caused by physiological factors, namely a decrease in body function due to the aging process so many noncommunicable diseases appear in the elderly. Methods: This study was an experimental study that examines the effect of hypertension exercise on blood pressure in the elderly with hypertension using a quasi-experimental approach with a time series design. This study used purposive sampling, with a total of 30 people. Before being given treatment, respondents were given an observation sheet (pretest) to measure the scale or blood pressure. Then given hypertension exercise and continued with giving a second observation sheet (posttest) to determine the scale or the respondent's blood pressure after the hypertension exercise 3 times with an interval of 1 week. Results: Before being given hypertension exercise, pretest data showed that the average blood pressure was 150/90. After being given hypertension exercise, it showed an average of 120/80. There was an effect of hypertension exercise on blood pressure in the elderly with hypertension at Wreda Tresna Budi Luhur Social Institution. Conclusion: Hypertension exercise performed every week for 3 times can reduce blood pressure in hypertensive elderly at Wreda Tresna Budi Luhur Social Institution in Bantul Yogyakarta.